Keefektifan insektisida cyantraniliprole terhadap hama penggerek buah kopi ( Hypothenemus hampei) pada ko pi arabika ( Effectiveness cyantraniliprole against coffee berry borer (Hypothenemus hampei)on arabica coffee. - Soekadar Wiryadiputra (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2012)
A trial on cyantraniliprole 10% against coffee berry borer (Hypothenemus hampei) has been conducted on arabica coffee at Kalibendo Estate, in Banyuwangi regency, East Java. The altitude of the estate is about 650 m above sea level (asl.) and belongs to B type of climate classification according to Schmidt and Ferguson. Composite variety of arabica coffee at about four years old planted at the location was used as plant materials. Five levels of cyantranilprole dosage and two compared insecticides i.e: carbaryl 85% and lamda cyhalothrine 25 g/L have been applied as treatments and each treatment is replicated four times. Infestation of coffee berry borer (CBB) has been observed on berries in the field as well as on harvested berries and green coffee. The results revealed that cyantraniliprole 10% was very effective in suppressing infestation and population of CBB on coffee berries in the field as well as on harvested parchment and green coffee. The dosage of 2,000 ml/ha was the most effective and the highest level of efficacy against CBB until the last observation during 14 weeks trial. Application of cyantraniliprole 10% also has increased the production of green coffee harvested. The highest increase occurred on the treatment of cyantraniliprole 10% with a dosage of 1000 ml/ha, which it reached 62.87% higher compared to untreated treatment. Carbaryl and lamda cyhalothrine have effectiveness and efficacy level lower than the highest dosage of cyantraniliprole 10%.